Ganesha, Surya and Chandra figures on a panel - Temples of India Project Team (Jio Institute, 2024)
The trio of Ganesha, Surya, and Chandra is one of the several loose sculptures that were affixed on the later structures at the site. The three figures may have once been part of a larger panel depicting the nine heavenly bodies or the navagraha. While the dancing Ganesha is four-armed, the images of Surya and Chandra have only two arms, broken in both cases. The erect uplifted posture, or the samabhanga, of Surya contrasts with the dynamic posture of Ganesha and the tribhanga posture of Chandra. Both Surya and Chandra have broken heads but can be identified through the boots of the former image and the depiction of a crescent behind the neck of the latter.